Ring compression properties of SiCf/SiC composites prepared by chemical vapor infiltration. Issue 18 (15th December 2018) - Li, Yue; Chen, Zhaoke; Zhang, Ruiqian; He, Zongbei; Wang, Haoran; Wang, Linjing; Liu, Guiliang; Fu, Daogui; Xiong, Xiang
Abstract: SiC fiber reinforced SiC matrix (SiCf /SiC) composites prepared by chemical vapor infiltration are one of promising materials for nuclear fuel cladding tube due to pronounced low radioactivity and excellent corrosion resistance. As a structure component, mechanical properties of the composites tubes are extremely important. In this study, three kinds of SiCf preform with 2D fiber wound structure, 2D plain weave structure and 2.5D shallow bend-joint structure were deposited with PyC interlayer of about 150–200 nm, and then densified with SiC matrix by chemical vapor infiltration at 1050 °C or 1100 °C. The influence of preform structure and deposition temperature of SiC matrix on microstructure and ring compression properties of SiCf /SiC composites tubes were evaluated, and the results showed that these factors have a significant influence on ring compression strength. The compressive strength of SiCf /SiC composites with 2D plain weave structure and 2.5D shallow bend-joint structure are 377.75 MPa and 482.96 MPa respectively, which are significantly higher than that of the composites with 2D fiber wound structure (92.84 MPa). SiCf /SiC composites deposited at 1100 °C looks like a more porous structure with SiC whiskers appeared when compared with the composites deposited at 1050 °C. Correspondingly, the ring compression strength of the composites deposited at 1100 °C (566.44 MPa) is higher than that of the composites deposited at 1050 °C (482.96 MPa), with a better fracture behavior. Finally, the fracture mechanism of SiCf /SiC composites with O-ring shape was discussed in detail.